Konsep Manajemen Kesiswaan dalam Al-Qur'an dan Hadits pada Lembaga Pendidikan Pesantren: Tinjauan Literatur - Falaach, Muchammad Fajeril; Fauji, Imam (Lembaga Yasin AlSys, 2025)
In this research, the author discusses the concept of student management from the perspective of the Al-Quran and Hadith, which are the guidelines and references of Muslim life. Student management is important and needs to be considered in achieving organizational goals, especially in educational institutions. Although the Al-Quran and Hadith do not include student management issues in detail. However, student management is something that needs to be studied more deeply. The method used in this research is System Literature Review (SLR), data obtained through a review of articles that have been published. The author will analyze the verses of the Koran and hadith related to student management and its implications for student management in pesantren. The results showed that the principles of student management in the Qur'an include planning (QS. Al-Hasyr: 18), character building (QS. Luqman: 13-19), and moral development (QS. An-Nahl: 125). In addition, the Hadith also emphasizes the importance of knowledge, exemplary leaders, and time management as an integral part of student management. The findings provide a practical contribution for pesantren in creating an educational environment that is conducive, based on Islamic values, and relevant to the needs of the modern era. This research also emphasizes the importance of strengthening spiritual values and character in the Islamic education system. Thus, student management based on the Qur'an and Hadith can be an effective, balanced, and sustainable management model in pesantren.